Interpersonal Meaning of Mangupa Towards Dalihan Na Tolu Tapanuli Selatan in Medan - Daulay, Irma Khoirot (Association of Language Teachers in Southeast Asia (ALTSA), 2021)
The recent study analyzed the interpersonal meaning of